Protocol to measure endogenous GlcNAc-1-phosphotransferase activity in SK-MEL-30 cells - Balraj Doray; Danielle Henn; Xi Yang; Ming Li; Patricia Dickson (STAR Protocols, 2025)
Summary: GlcNAc-1-phosphotransferase (GNPT) is the key enzyme for tagging lysosomal hydrolases with the mannose 6-phosphate moiety for delivery to the lysosome. Here, we present the assay for measuring endogenous GNPT activity in SK-MEL-30 cells. We provide details for preparing the [3H]UDP-GlcNAc donor substrate and conditions for the enzymatic transfer of [3H]GlcNAc-1-P to the methyl α-D-mannopyranoside acceptor (α-MM). We then describe the chromatography steps to specifically separate the [3H]GlcNAc-1-P-αMM GNPT reaction product from unreacted [3H]UDP-GlcNAc that is bound to the quaternary aminoethyl (QAE) Sephadex A-25 matrix.For complete details on the use and execution of this protocol, please refer to Doray et al.1 and Yang et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.